1982
DOI: 10.1084/jem.156.6.1665
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Ia antigen in rat epidermal cells and gut epithelium by immunological stimuli.

Abstract: The expression of Ia antigen in rat keratinocytes and gut epithelium was found to be inducible by a variety of immunological stimuli. Graft-vs.-host disease (GvHD) was accompanied by the appearance of Ia antigen in both sites, whereas local immunological stimuli, such as a contact-sensitizing agent applied to the skin and Trichinella spiralis infection of the gut, caused the expression of Ia antigen confined to the sites of contact of these stimuli with the tissues involved. Both T helper and T cytotoxic/suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
1

Year Published

1984
1984
1990
1990

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(56 citation statements)
references
References 23 publications
2
53
1
Order By: Relevance
“…This also agrees with the appearance of Ta on various cell types, including gut epithelium, in rats injected with selected subsets of semi-allogeneic T lymphocytes (39). In contrast, IL3 release is consistently higher with L3T4+ than with Lyt 2+ cells, a fact which correlates well with the appearance ofgut MCs in GVHR elicited in nonirradiated mice (since MC precursors are radiosensitive); MCs, which differentiate from precursors present in the gut wall under the effect of IL3 release (7,40) Finally, the arrival of donor T cells in the host mucosa has effects other than the elicitation of epithelial damage.…”
Section: Discussionsupporting
confidence: 73%
“…This also agrees with the appearance of Ta on various cell types, including gut epithelium, in rats injected with selected subsets of semi-allogeneic T lymphocytes (39). In contrast, IL3 release is consistently higher with L3T4+ than with Lyt 2+ cells, a fact which correlates well with the appearance ofgut MCs in GVHR elicited in nonirradiated mice (since MC precursors are radiosensitive); MCs, which differentiate from precursors present in the gut wall under the effect of IL3 release (7,40) Finally, the arrival of donor T cells in the host mucosa has effects other than the elicitation of epithelial damage.…”
Section: Discussionsupporting
confidence: 73%
“…This level of expression, while well below that seen in the GvHD rats, exceeded that seen in the negative controls that were not reconstituted. In ... cells in gut, skin, and other tissues that do not normally exhibit it (34). GvHD induced in neonatal animals affects the development of normal cerebellar morphology and neuronal maturation (35); however, the mechanism by which this occurs remains unknown.…”
Section: Resultsmentioning
confidence: 99%
“…It is also observed that about 5% of the intestinal absorptive cells penetrate the basal lamina in reverse, protruding their processes into the lamina propria; here a similar association of the absorptive cells with the cells of the immune system takes place. In this context, it is noteworthy that the intraepithelial lymphocytes are mostly T cells in the mouse, rat and human (FERGUSON, 1977;SELBY et al, 1981;LYSCOM and BRUETON, 1982;DILLON and MACDONALD, 1984), and that the absorptive cells of villi possess major histocompatibility complex (MHC) la antigens that are essential for antigen recognition by T cells (SCOTT, 1980;BARCLAY and MASON, 1982;MAYRHOFER et al, 1983 either hydrolytic procedure (DESAKI et al, 1984) or enzymatic digestion (Fig. 16).…”
Section: Cells Of the Immune Systemmentioning
confidence: 99%